1999
DOI: 10.1007/s004210050591
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow velocity responses to hypoxia in subjects who are susceptible to high-altitude pulmonary oedema

Abstract: Cerebral blood flow increases on exposure to high altitude, and perhaps more so in subjects who develop acute mountain sickness. We determined cerebral blood flow by transcranial Doppler ultrasound of the middle cerebral artery at sea level, in normoxia (fraction of inspired O2, F(I)O2 0.21), and during 15-min periods of either hypoxic (F(I)O2 0.125) or hyperoxic (F(I)O2 1.0) breathing, in 7 subjects with previous high-altitude pulmonary oedema, 6 climbers who had previously tolerated altitudes between 6000 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…Velocities in the MCAs increased immediately upon acute exposure to high altitude, which was the same as the results reported in several studies (Berre et al 1999 ; Lucas et al 2011 ; Rootwelt et al 1986 ; Rudzinski et al 2007 ). We also found that the velocities of BA and VAs, which constitute the posterior cerebral circulation, were significantly altered from 500 to 3,700 m, which is partially consistent with a previous study (Huang et al 1987 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Velocities in the MCAs increased immediately upon acute exposure to high altitude, which was the same as the results reported in several studies (Berre et al 1999 ; Lucas et al 2011 ; Rootwelt et al 1986 ; Rudzinski et al 2007 ). We also found that the velocities of BA and VAs, which constitute the posterior cerebral circulation, were significantly altered from 500 to 3,700 m, which is partially consistent with a previous study (Huang et al 1987 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, the controversy result that CBF increases with acute hypoxia has been reported (Lassen 1992 ). Although a depression chamber study of 10 subjects has showed that AMS is not related to CBF (Baumgartner et al 1999 ), CBF velocity responses to hypoxia in subjects who are susceptible to high-altitude pulmonary edema have been revealed (Berre et al 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 At this time, few studies exist which use cerebral near infrared (NIR) spectroscopy successfully at high altitude [11][12][13][14][15][16][17] and only some investigators have measured the blood fl ow velocity in cerebral arteries. [18][19][20][21][22][23][24] However, the results are different and not clear in detail yet. In a previous study by our research group, we found, for the fi rst time, reproducible data using NIR spectroscopy during a trekking tour in the Nepal Himalayas.…”
Section: Introductionmentioning
confidence: 99%
“…Berre (Berre et al 1999) demonstrated a 20-23% increase in middle cerebral artery velocity with hypoxia but found no significant difference between AMS-susceptible and AMS-resistant subjects. Using 15 O-H 2 O PET Buck (Buck et al 1998) reported no change in quantified global cerebral blood flow after acute (20 minute) exposure to 3,000 m, but a 36% increase (+7.2 ml/100g/ min) at 4,500 m (i.e.…”
Section: Comparison With Other Measures Of Cerebral Blood Flowmentioning
confidence: 99%